Pengembangan E-Module Keanekaragaman Makhluk Hidup Berbasis PBL Bermuatan Kearifan Lokal dan Pengaruhnya terhadap Keterampilan Berpikir Kritis, Pemecahan Masalah, dan Sikap Lingkungan - Rosidi, Adelina; Rohman, Fatchur; Novianti, Vivi; Hariadi, Ismawan (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This research aims to develop a PBL-based e-module containing local wisdom that is valid, practical and effective for improving students' critical thinking skills, problem solving and environmental attitudes. This type of research is research and development (Research & Development) using the Lee & Owens (2004) model which consists of 5 stages, namely assessment and analysis, design, development, implementation, and evaluation. The subjects used in this research were 36 students in class X.B and 36 students in class X.E at SMA Negeri 1 Narmada. The research instruments used consisted of expert validation sheets, practicality assessment sheets, and tests of students' critical thinking skills, problem solving, and environmental attitude questionnaires. The research results show: 1) the e-module meets the validity requirements based on the assessment of material experts with an average validity of 100% which is in the very valid category, media and teaching materials experts are 98% in the very valid category, and biology education practitioners are 99% in the category very valid. The e-module developed meets the practicality requirements based on the results of trials per person, namely 89% in the very practical category, small group trials, namely 91% in the very practical category and field trials, namely 89% in the very practical category; and 2) test the effectiveness of the e-module using the ANCOVA hypothesis test showing that the e-module is effective in improving students' critical thinking skills, problem solving and environmental attitudes. Based on these results, it can be concluded that the PBL-based e-module contains the local wisdom of Sesaot Village in the form of using plants as medicinal plants and their conservation efforts meet the criteria of being valid, practical and effective for improving students' critical thinking skills, problem solving and environmental attitudes.